The Importance of Business Process Management for Transport Department of Logistics Companies - Narvaez Pereda, Claudia (2018)
Applying Business Process Management in transport area of logistics companies brings the chance to develop the processes through web systems, desktop systems, apps, to name a few; focused on managing the resources (vehicles and drivers) in an organized way. This model is based on accomplishing synergy, keeping continuous improvement and giving a soon answer to clients.